Cooperative work and critical thinking of technological higher education teachers in Peru (GnosisWisdom, 2023)
The study constituted a basic investigation, it started from the problem: What is the relationship between cooperative work and critical thinking in higher technological education teachers of a Regional Directorate of Education in Peru? The objective was: to determine the degree of relationship that occurs between cooperative work and critical thinking in higher technological education teachers of a Regional Directorate of Education in Peru. With a population of 838 and a sample of 90 teachers from Institutes of Higher Technological Education of a Regional Directorate of Education of Peru. The scientific method was used as a general method and the descriptive method as a specific method, with a correlational design; having cooperative work and critical thinking as variables; using observation and the virtual respondent as a technique and the cooperative work and critical thinking questionnaire as an instrument, the results of which were statistically analyzed using Pearson's r statistic, determining a significant relationship between cooperative work and critical thinking with a r = 793**. Likewise, the study shows the relationship of cooperative work with the dimensions of critical thinking, as information management of critical thinking reaches a significant r = 0.774 ** correlation, with the dimension of reflection capacity a r = 0.511 ** significant correlation and with the dimension of decision-making capacity r=0.669** a significant correlation.
Keywords: Cooperative work; critical thinking; higher education